Production of urea with boron to reduce nitrogen losses and improve crop yields - Stelutti, Ingrid Martins (2025)
Urea [CO(NH2)2] is the most widely used nitrogen fertilizer in the world. However, its surface application to the soil causes nitrogen (N) losses through ammonia volatilization (NH3), which reduces the availability of N to plants and the efficiency of nitrogen fertilization. This study hypothesizes that the production of urea with boron (B) will result in a multinutrient fertilizer with increased efficiency, reduced nitrogen (N) losses, and enhanced crop productivity. This work aimed to produce, characterize, and evaluate fertilizers based on granulated urea coated with B sources of different solubilities (boric acid-A, sodium octaborate-OB, sodium tetraborate-TB, ulexite-UL, colemanite-CL, and mix-BT + CL), associated (UrNBPT) or not (Ur) with the urease inhibitor N-(n-butyl) thiophosphoric triamide (NBPT). The activity of the urease enzyme, N losses due to NH3 volatilization, nitrous oxide (N2O) emissions, nitrate (N3-O) leaching, biomass, and B accumulation by maize in a controlled environment were evaluated. In the first study, carried out by granulating urea with B, a reaction between urea and B was observed during fertilizer production. Incorporating B into the urea granules increased the hardness and hygroscopicity of the fertilizers. Urea lost 26% of the N applied via fertilizer, while the UrAB, UrUL, and UrMix formulations reduced NH3 losses by 37-42% compared to Ur. The UrNBPT and B formulations, except UrNBPTAB, reduced NH3 losses by 91-94% compared to Ur, while the reduction caused by NBPT was 82%, showing that the B sources increased the inhibitor\'s efficiency in reducing NH3 losses. The effects of B on reducing N2O emissions were unclear, and it is suggested that it be better evaluated in future studies. In the second study, urea was coated with B sources, and it was observed that NBPT and OB increased the hygroscopicity of the fertilizers. TB and UL inhibited urease activity compared to the other B sources. Except AB, the other B sources reduced accumulated NH3 losses compared to Ur, as did NBPT (40% reduction). Plant biomass was significantly higher for the treatments with UL and Mix as a coating for Ur and UrNBPT, and the association of UrNBPT with B increased the B content in the plants. The addition of B to urea, both in granulation and coating, has shown promise for producing a multinutrient fertilizer with lower N losses and higher biomass production in maize.